2023
DOI: 10.3390/nu15040826
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of the Subgingival Microbiome and Relation to Periodontal Disease in Association with Obesity and Overweight

Abstract: Obesity causes gut dysbiosis; nevertheless, little is known about the oral microbiome. We aimed to identify differences in the subgingival microbiota influenced by body weight and periodontal status. Patients (n = 75) recruited at the University Dental Hospital Sharjah, United Arab Emirates, were distributed into three equal groups (healthy weight, overweight, and obese) sub-divided into having either no-mild (NM) or moderate-severe (MS) periodontitis. Subgingival plaques were collected. Microbiota were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 67 publications
0
11
0
1
Order By: Relevance
“…These results suggest that Selenomonas may play an important and significant role in a two-way system that influences the development of overweight and obesity, although this may not be the only periodontal pathogen with specific properties that influence this relationship. For example, other studies have demonstrated that additional periodontal pathogens, including Aggregatibacter actinomycetemcomitans , Treponema denticola, and Tannerella forsythia, may also be observed to have different prevalence between normal weight and overweight or obese patients with periodontal disease [ 52 , 53 ]. However, the bidirectional relationships observed between these pathogens and systemic diseases, such as diabetes, metabolic syndrome, and obesity, appear to be more functionally related to inflammatory cytokines and the inhibition of other metabolic pathways rather than on directly increasing caloric recovery from dietary intake, as has been demonstrated with Selenomonas [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that Selenomonas may play an important and significant role in a two-way system that influences the development of overweight and obesity, although this may not be the only periodontal pathogen with specific properties that influence this relationship. For example, other studies have demonstrated that additional periodontal pathogens, including Aggregatibacter actinomycetemcomitans , Treponema denticola, and Tannerella forsythia, may also be observed to have different prevalence between normal weight and overweight or obese patients with periodontal disease [ 52 , 53 ]. However, the bidirectional relationships observed between these pathogens and systemic diseases, such as diabetes, metabolic syndrome, and obesity, appear to be more functionally related to inflammatory cytokines and the inhibition of other metabolic pathways rather than on directly increasing caloric recovery from dietary intake, as has been demonstrated with Selenomonas [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Linear discriminant analysis (LDA) effect size (LEfSe) was used to detect biomarkers from microbial profiles ( 31 ) using the Microbiome Analyst 2.0 platform (McGill, Canada), which was also used to generate the graph of relative abundance and the heatmap for groups comparison ( 32 ). Venn diagrams were generated to compare the taxa exhibiting significant differences based on the LDA analysis for the identification of shared and unique OTUs ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…The full-length bacterial 16S rRNA gene (1500 bp) was sequenced with Mk1C Oxford Nanopore sequencer using 16S Barcoding kit 1-24 (SQK-16S024; Oxford Nanopore Technologies, UK) 18 . DNA was amplified by PCR using LongAmp™ Taq 2 × Master Mix (New England Biolabs, UK), and purified by AMPure XP beads (Beckman Coulter, USA), then quantified by Qubit 2 (Thermo Scientific, USA).…”
Section: Saliva Sample Collection Processing and Dna Extractionmentioning
confidence: 99%
“…Operational Taxonomic Units (OTUs) were analyzed using Microbiome Analyst 2.0 platform (McGill, Canada) 21 , which was also used for other downstream analyses. Linear discriminant analysis (LDA) effect size (LEfSe) was used to detect biomarkers from microbial profiles, at an LDA threshold of 2 18 , 22 . For α-diversity, different indices were used including Shannon and Simpson diversity (richness, and evenness measures), Chao1 (estimator for diversity from abundance data), ACE (Abundance-based Coverage Estimator), and Observed Species (counts of unique OTUs per sample).…”
Section: Saliva Sample Collection Processing and Dna Extractionmentioning
confidence: 99%